Relationship between gut microbiota, probiotics, and type 2 diabetes mellitus - Salgaço, Mateus Kawata [UNESP]; Oliveira, Liliane Garcia Segura; Costa, Giselle Nobre; Bianchi, Fernanda [UNESP]; Sivieri, Katia [UNESP] (Springer Nature, 2019)
The worldwide prevalence of type 2 diabetes mellitus (T2DM) is constantly increasing, and it has become a major concern, with several implications for public health, economy, and social well-being. It is well-known that several factors such as lifestyle, increased intake of fat and sugar-rich foods, and host genetics can lead to T2DM. Some recent studies have suggested that the composition of the intestinal microbiota can trigger T2DM. Since then, considerable effort has been made to understand the link between the composition of intestinal microbiota and T2DM, as well as the role of probiotics in modulation of intestinal microbiota. This mini-review summarizes the major findings and discusses the close relationship between intestinal microbiota, probiotics, and T2DM.
Keywords: Chronic disease; Gut microbiota; Probiotic; Type 2 diabetes